qTrustNet Virtual Private Network (VPN): Enhancing Security in the Quantum Era - Hyoungsub Shim; Bongho Kang; Haejung Im; Duhyun Jeon; Seok-Min Kim (IEEE Access)
This paper introduces qTrustNet VPN, a next-generation Virtual Private Network (VPN) designed to enhance security in the quantum era. As traditional encryption methods face obsolescence due to the advent of quantum computing, there is an urgent need for more robust security solutions. qTrustNet VPN addresses this need by ensuring the confidentiality and integrity of data transmission through the WireGuard protocol, known for its simplicity and high performance. At the core of qTrustNet VPN’s enhanced security is the integration of a Post-Quantum Cryptography (PQC) algorithm, developed by the National Institute of Standards and Technology (NIST). This PQC algorithm is designed to withstand the decryption capabilities of quantum computers, thus providing long-term security. To further bolster security, the encryption key of the PQC algorithm is protected using Physically Unclonable Function (PUF) technology. PUFs offer a hardware-based security mechanism that is resistant to cloning and tampering, ensuring that the encryption keys remain secure against both classical and quantum attacks. This innovative combination of WireGuard protocol, PQC algorithms, and PUF technology creates a VPN system with significantly improved security features. To validate its effectiveness, the performance of the proposed qTrustNet VPN was rigorously evaluated in a 10GbE NIC network environment. The results demonstrated a remarkable throughput of up to 8.5 Gbps, ensuring high-speed data transmission capabilities. Additionally, the latency was measured at 1ms or less, highlighting the system’s efficiency in maintaining low-latency communication. In summary, qTrustNet VPN represents a significant advancement in VPN technology, offering robust security features tailored for the quantum era while maintaining high performance and low latency. This paper details the design, implementation, and performance evaluation of qTrustNet VPN, showcasing its potential to secure data transmission against emerging quantum threats.